Records in tuberculosis detection: perception of health professionals - Jéssica Oliveira Tomberg; Lílian Moura de Lima Spagnolo; Natali Basilio Valerão; Martina Dias da Rosa Martins; Roxana Isabel Cardozo Gonzales
Abstract Objective: to know the perception of health professionals about the records produced in the detection of symptomatic respiratory symptoms of tuberculosis. Method: a qualitative study carried out in the municipalities of Sapucaia do Sul and Pelotas (Rio Grande do Sul state). Data were collected between January 2013 and March 2014 with 37 health workers through a semi-structured interview and analyzed in light of the Bardin Content Analysis. Results: three categories emerged, one of which pointed out the potentialities of tuberculosis detection records for case follow-up and two verified the obstacles related to inadequate, excessive duplication of information, requiring physical space for storage and loss of data. records. Conclusion and implications for the practice: the professionals recognize the importance of registries in the detection of tuberculosis, but point out obstacles that make it impossible to apply them in daily life. This information can help municipal managers to reassess the instrument by making advances in the operability of registries in the detection of tuberculosis.